Decision Support System for Determining Recipients of Subsidized Foodstuffs for Poor Families Using the Simple Addictive Weighting Method - Afifah Sagita Pratiwi; Gushelmi; Sepsa Nur Rahman (Universitas Putra Indonesia YPTK Padang, 2024)
Technology is increasingly becoming a necessity that must be met, both in the world of education and in the world of business and social, especially information technology is used not only as a support but also as a primary need that can be used to provide information quickly. In accordance with what has been determined to obtain Subsidized Food, criteria are needed to determine who will be selected to receive subsidized food. The distribution of subsidized food is distributed to underprivileged or poor citizens. To assist in determining who is eligible to receive subsidized food, a decision support system is needed. One method that can be used for Decision Support Systems is by using Simple Additive Weighting (SAW). In this study, a case will be raised, namely finding the best alternative based on predetermined criteria by using the SAW method to calculate the method in the case. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is those who are entitled to receive subsidized food based on the specified criteria. The study was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the poor. After the study was conducted, the results obtained were that there were 4 alternatives receiving Subsidized Food and the one with the highest value was alternative 5 with the name Yuhel Fentri with a value of 0.875.